IMPLEMENTASI DATA MINING CLUSTERING DALAM MENGUKUR KEPUASAN TERHADAP PELAYANAN PERPUSTAKAAN DI UNIVERSITAS PRIMA INDONESIA - Winda Nia Purba; Rinaldi Syahputra; Fine Reza Nainggolan; Gabriel Immanuel Manullang (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This research aims to measure student satisfaction with Prima Indonesia University library services using data mining methods. Clustering techniques are used to group student satisfaction data based on various attributes such as service quality, resource availability, facility comfort, and interaction with library staff. Data was collected through questionnaires distributed to students. The clustering results revealed significant patterns in student satisfaction, which were analyzed to identify key factors influencing satisfaction levels. These results provide library managers with valuable insights for optimizing services and increasing user satisfaction. The application of clustering data mining has proven effective in helping libraries understand student needs and preferences and plan service improvements more accurately and efficiently.